2018
DOI: 10.1016/j.bbamem.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered lipid properties of the stratum corneum in Canine Atopic Dermatitis

Abstract: Skin barrier disruption plays a role in the pathogenesis of atopic dermatitis (AD) in humans. However, little is known about skin barrier (dys-) function in Canine Atopic Dermatitis. The properties of lipids located in the outermost layer of the skin, the stratum corneum (SC) are considered to be important for the barrier. In the present study the lipid composition and lipid organization of the SC of AD dogs and control dogs were examined. The lipid composition of lesional AD skin as compared to control skin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 51 publications
0
33
0
11
Order By: Relevance
“…We detected 392 lipids, the majority of which could not be readily identi ed. The lipids found included ceramides, which were different to those that have been previously identi ed as being important in canine SC, and were in relatively low abundance [10,11,13,24]. This suggests that there are many more lipids which may have a functional role in health and/or disease than previously identi ed.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We detected 392 lipids, the majority of which could not be readily identi ed. The lipids found included ceramides, which were different to those that have been previously identi ed as being important in canine SC, and were in relatively low abundance [10,11,13,24]. This suggests that there are many more lipids which may have a functional role in health and/or disease than previously identi ed.…”
Section: Discussionmentioning
confidence: 71%
“…It is not known how these variables may have impacted the lipid pro les obtained but it is known from human studies that skin lipids vary with age and gender [26,27,28]. Lipid pro les also vary between body sites [13] and, in an untargeted human study, lipids varied depending on sebaceous gland density [29]. In order to limit this variable in our study the body sites sampled were kept as consistent as possible but there was variation in the affected sites sampled, and it is not known if this may have in uenced the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Investigation of the CER organization within the biological environment has important role in the study of the skin barrier function, and studies have reported alteration of the CERs composition in impaired human and canine skin barrier. [31,32] To address CERs complexity researchers are continuously seeking for methods convenient to reveal mechanisms of biomolecular interactions in the cells. To use advantage of sensitivity and specificity of MRM methods in some studies semi-quantification and profiling of the CERs performed with scheduled-MRM approach resulted with detection of more than 1000 CER species.…”
Section: Esi-ms/ms Structural Characterization In Positive Ionisationmentioning
confidence: 99%
“…Allergic sensitization to environmental allergens is common and exposure to allergens can increase the severity of AD . Impairment of the skin barrier has been described in atopic dogs and increases the risk for epicutaneous sensitization . It is currently unknown how systemic drug treatment for canine AD affects the rate and frequency of new allergen sensitization.…”
Section: Introductionmentioning
confidence: 99%